Determinants of Job Satisfaction among Teachers in Nepal - Timalsina, Dhanishor (The Management Review, 2025)
This study aims to investigate the variables influencing private school teachers’ job satisfaction in Nepal, which is affected by various elements, including pay and incentives, working conditions, management support, workloads, job security, etc. Based on a questionnaire survey, the research employed a descriptive and causal comparative research design. For the self-administrative questionnaire survey, a total of 202 samples of teachers from various private schools were selected according to the judgmental basis of the researcher. KMO, Bartlett’s test, regression analysis, correlation, reliability analysis, and descriptive analysis have all been performed. This study demonstrates how teachers generally feel about their workload, managerial assistance, working conditions, job security, and pay and incentives. The study finds a strong and beneficial correlation between pay and incentive, working condition, management support, and job security, whereas there is no correlation exists between job satisfaction and workload. The private schools should prioritize improving working conditions, management support, job security, and pay and incentives to enhance teachers’ satisfaction while addressing workload-related challenges to mitigate dissatisfaction.